Early class self-preparation: a step ahead for a better learning experience / Hazwati Hashim - Hashim, Hazwati (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Attending class is not merely walking and sitting still while letting yourself wait for the instructor to tell you what you are expected to learn and do for the lessons learned that day. It is more than going through the same routine that students mostly expect to experience each day they go to class. Students are not fully aware of how important it is to get themselves well-prepared before attending a class. Generally, being well-prepared for class has more to do with how well you spend your time wisely, which has less to do with how much you spend your time preparing for the class. It has a similarity with the time you spend taking an examination, which means that the more time you spend studying, the more you will be well-prepared for the examination. A well-prepared class will enhance an active learning environment, increase students’ engagement in learning, stimulate learning interest, and encourage collaborative learning.